The comparative analysis of results of surgical treatment of myasthenia in the remote periods of disease - L. Zaslavsky; V. D. Kosachev; A. B. Khurshilov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
Based on long-term follow-up to perform comparative analysis of long-term results of surgical treatment of myasthenia. A retrospective analysis of long-term results of surgical treatment of 146 patients with myasthenia has been carried out. We used the modified Keynes classification to estimate the severity of myasthenia and to summarize the data relating to therapy volume and treatment results. In dependence on the type of thymus lesion patients were divided into two groups. Thymus hyperplasia was verified at — 106 (72.6 %) patients, tumor lesion of the thymus gland (thymoma) — at 40 (27.4 %) ones. The results were estimated in the following periods after thymectomy: 1—2 years, 3—4 years, 5—6 years, 7 — 9 years, 10—14 years, and over 15 years. Short- and longterm results of surgical treatment of myasthenia for the patients without tumor lesions of the thymus gland were significantly better. Positive effects of surgical treatment of myasthenia in patients with hyperplasia are observed after 1 year of surgery (p = 0.0023), and the best results are observed after 5 — 6 year of the disease, then after 7 — 9 year one notes some deterioration of state (p = 0.026). In the myasthenia patients with thymoma one notes the similar trends in dynamics of state, but in general, the results are significantly (p = 0.042) badly than in the group of the patients with hyperplasia. Starting from the first year after operation treatment the patients with myasthenia with thymus hyperplasia have statistically significant (p = 0.048) decrease of average doses of glucocorticoids, and anticholinesterase drugs. The statistically best treatment results were noted for the patients operated at the first year of the disease. Positive result of surgical treatment of myasthenia is noted both in the short- and long-term period and at thymomas. In the group of patients with thymoma one has noted significantly badly results in comparison with group of hyperplasia. It is necessary to perform surgical treatment in the first year of disease.